Side by side - Walsh, Jenni L. (Walsh, Jenni L. Novel of Bonnie and Clyde., 2018)
Texas: 1931. It's the height of the Great Depression, and Bonnie is miles from Clyde. When Clyde returns from prison damaged and distant, unable to keep a job, and dogged by the cops, Bonnie knows the law will soon come for him. But there's only one road forward for her. If the world won't give them their American Dream, they'll just have to take it.